2000
DOI: 10.1111/j.1574-6941.2000.tb00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbes involved in dissimilatory nitrate reduction in the human large intestine

Abstract: Nitrate-limited batch cultures, incorporating 20 different fermentation substrates and inoculated with human faeces, mainly selected for the growth of enterobacteria. The microbial diversity involved was determined by a combination of phenotypic and genotypic procedures. Continuous culture with lactate as the sole electron donor selected for similar micro-organisms, but when antibiotics were incorporated to inhibit Escherichia coli and lactate was replaced with choline, there was a wider microbial diversity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…27 Despite its natural abundance in food, nitrate has been considered to have negative health effects, due to the fact that it can be transformed into nitrite (which has an MCL of only 1 mg L −1 ) by bacterial nitrate reductases (NR) in the oral cavity 2830 and gastrointestinal tract. 3133 …”
Section: Nitrate Reductionmentioning
confidence: 99%
“…27 Despite its natural abundance in food, nitrate has been considered to have negative health effects, due to the fact that it can be transformed into nitrite (which has an MCL of only 1 mg L −1 ) by bacterial nitrate reductases (NR) in the oral cavity 2830 and gastrointestinal tract. 3133 …”
Section: Nitrate Reductionmentioning
confidence: 99%
“…Allison and Macfarlane [26] reported that DNRA is the major pathway for nitrate reduction by the fecal microbiota. Identification based on phenotype and genotype showed that Clostridium ramosum , Bacteroides vulgates, and the enterobacteriaceae were mainly capable of DNRA [27]. These species are representative for the dominant groups of the fecal microbiota [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Three possible pathways were considered (i) L-arginine as substrate for NO synthase, (ii) denitrification to nitrogen gas and (iii) dissimilatory nitrate reduction to ammonium (DNRA). The latter was considered as fermentative nitrate reduction is expected under gastrointestinal conditions however no relation with NO production has been considered [26, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…In vivo conditions may have affected bacterial NO production by propionibacteria as compared with in vitro ones, and have stimulated NO production from TL15. Alternatively, considering that the commensal intestinal bacteria intensively reduce nitrate to ammonia [33], the in vivo conditions may also have inhibited NO production by TL223 due to competition for nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…Production of bacterial NO has been extensively described in established environmental denitrifiers such as Pseudomonas and Paracoccus [49] but it is very unusual for bacteria which are encountered in the intestine. Indeed, the commensal intestinal flora can efficiently reduce nitrate and nitrite but this phenomenon occurs mainly via a dissimilatory reaction where ammoniac is the final product of nitrite reduction [33]. One exception is some enteric bacteria, which can produce small amounts of NO from nitrite reduction [13].…”
Section: Discussionmentioning
confidence: 99%